Analysis of determining superior vegetable commodities in Batu City in 2016-2020 - Yeny Kristina Widyastuti; Ary Bachtiar; M. Zul Mazwan (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: Batu City is one of the largest vegetable supply cities in East Java. This is a concern of the government to continue to develop the existing potential considering that the agricultural sector plays a large role in agriculture development in Batu City. The research aims to identify superior vegetable commodities with high competitiveness to improve farmers' welfare. The research was conducted in Batu City from August to October 2022. Methods: The method used in the research was a Literature Study using secondary data obtained from the East Java Central Bureau of Statistics and Batu City as well as from various journals. The analysis tools use Microsoft Excel with the analysis method using Location Quotient (LQ). Results: The results showed that the superior commodity in Batu City was cauliflower with an average LQ value of 9.3957. Garlic 5.6996. Chayotes squash 5.2903. Chickpeas 3.6315. Carrots 3.0185. Petsai 2.8091. Tomatoes 2.7492. Peppers 2.6474. Eggplant 1.8262. Mushrooms 1.7588. Red beans 1.6610. Scallions 1.4679. Cucumber 1.4558. Conclusion: Commodities included in LQ>1 are leeks, garlic, string beans, mushrooms, red beans, cauliflower, cucumber, chayote, peppers, Chinese cabbage, eggplant, tomatoes, and carrots. The commodities of shallots, spinach, large chilies, bird's eye chilies, long beans, kale, potatoes, cabbage, and radishes are not included in the superior commodities. Determining the right superior vegetable commodities can have positive impacts on farmers' income, increase product supply to the market, and improve people's quality of life.